DAMPAK IMPLEMENTASI PROGRAM MAKAN BERGIZI GRATIS TERHADAP KONSENTRASI BELAJAR SISWA DI SMA NEGERI 2 SUKOREJO - Martina, Titi; Wijayanti, Tutik (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Education plays a crucial role in developing quality human resources. The success of the learning process is influenced not only by academic aspects but also by the nutritional status of students. The purpose of this study was to examine how the implementation of the Free Nutritional Meal Program impacts student learning concentration at SMA Negeri 2 Sukorejo. The study involved the principal, teachers, and students as research subjects, using a descriptive qualitative approach with a purposive sampling technique. Data were collected through interviews, observation, and documentation. Data validity was tested using source and technique triangulation, while the data analysis process referred to the Miles and Huberman model, which includes data reduction, data presentation, and conclusion drawing. The results showed that the MBG program was implemented systematically through the stages of planning, distribution, consumption, and evaluation with the active involvement of the school. This program had a positive impact on student learning concentration, as indicated by increased learning focus, reduced distractions due to hunger, and increased active student participation in the learning process. Thus, the MBG program not only functions to meet nutritional needs but also contributes to improving the quality of the learning process, particularly in the aspect of learning concentration.